OPTIMASI PROSES PENGERINGAN KOPI DI PABRIK KOPI PTPN XII GUMITIR DENGAN MENGGUNAKAN MASON DRYER - Rusli Hidayat; Firdaus Ubaidillah; Hadi Siswanto (Universitas Jenderal Soedirman, 2018)
Coffee Processing Plant of the PTPN XII Gumitir is a coffee drying factory that was built in 1910 using a giant barch dryer called Mason Dryer as many as four units, each of which has a capacity of 20 tons, so factory is capable of processing 80 tons for a single simultaneous process. The ambient temperature used is 120oC with a residency time of 18 hours and desirable level of reduction in water content of 9%. To optimize the process, a mathematical model of the process is needed to predict energy use, heat distribution (heat profile in coffe beans) and residency time (heat penetration time required by coffee beans). Existing process models are still limited to models for drying the coffe beans. To optimize the process, a heat transfer temperature from ambient temperature (heating temperature) is neededto enter the Mason Dryer which function as the ambient temperature of the coffee beans at each location/ position of the coffee beans in Mason Dryer. With the discoveryof the model for ambient temperaturewill complement the existing model.